Buenas prácticas periodísticas: Cobertura informativa sobre la despenalización del aborto por violación - Sánchez León, Alisson Mercedes (2022)
The case study analyzed good journalistic practices in news coverage on the decriminalization of abortion for rape in the commercial media El Universo, the public media Plan V, and the community media Wambra Ec. The information will be extracted through their official websites, which will demonstrate the informative approach that is carried out depending on the type of media. It will identify and determine the good journalistic practices that these media have used. With the use of the analytical method, the objectives were met, and the observation sheets and expert criteria developed by a professional with legal expertise and a social communicator with extensive professional experience were used as research tools. The results indicate that only the commercial media was able to carry out a wide and complete coverage of the events analyzed. However, the contents of all the analyzed media met most of the criteria evaluated, highlighting that if they exist, good journalistic practices are used in the Ecuadorian media regardless of the typology to which they belong.